Superalloys 2012 (Twelfth International Symposium) 2012
DOI: 10.7449/2012/superalloys_2012_197_204
|View full text |Cite
|
Sign up to set email alerts
|

A New Single Crystal Superalloy for Power Generation Applications

Abstract: The properties of a newly developed single crystal superalloyknown as STAL-15 -is described which is suitable for use in first stage blades of industrial gas turbines (IGTs). With 15 wt.% Cr and 4.55 wt.% Al, the alloy combines good corrosion and oxidation resistance with sufficient creep and fatigue performance. Traditionally, polycrystalline alloys such as IN792 and IN738LC or the single crystal alloy PWA-1483 have been used for this application; unfortunately they display only limited resistance to environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 13 publications
1
26
0
Order By: Relevance
“…% Si increases the TMF by a factor of 2. In other studies, it has been shown that the addition of Si influences the formation of detrimental TCP phases during high temperature exposure, see [117]. However, it seems that the addition of 0.25 wt.…”
Section: Propertiesmentioning
confidence: 94%
See 3 more Smart Citations
“…% Si increases the TMF by a factor of 2. In other studies, it has been shown that the addition of Si influences the formation of detrimental TCP phases during high temperature exposure, see [117]. However, it seems that the addition of 0.25 wt.…”
Section: Propertiesmentioning
confidence: 94%
“…In this thesis, STAL-15 is the subject of both Papers VII and VIII. Table 3 displays the chemical composition of STAL-15 and for a detailed description of the alloy development history of this alloy the reader is referred to [117]. It should be noted that during its development, the alloy was first called SCA425 and later SCA425+, before being named STAL-15, and there are some small differences in chemical compositions between these forms.…”
Section: General Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…These prior studies did not address oxidation directly. Other more recent high Cr, but lower Al, single crystal alloys were developed (SCA425/STAL-15) to promote Cr2O3 scales for corrosion resistance in stationary gas turbines and helium reactors [15][16][17]. In the present program higher Mo contents have been explored while eliminating W. Mo is a powerful solid solution strengthener, but with a density much closer to Ni than other refractory strengthening elements, such as Re and W. According to the fundamental design study, Mo is about 3× the cost of W, but are both relatively inexpensive for refractory metals [14].…”
Section: Introductionmentioning
confidence: 99%